Cluster Randomized Controlled Trials (CRCTs) in Evidence-Based Dentistry - Francesco Chiappelli (Wolters Kluwer Medknow Publications, 2012)
A cluster randomized controlled trial (CRCT) is a type of randomized controlled trial in which groups of subjects (as opposed to individual subjects) are randomized. In this paper, we discuss the fundamentals of CRCT, its statistical power, and the implications of this design in context of comparative effectiveness and patient-centered research. We propose that, whereas CRCT pertain more specifically to effectiveness-driven decisions in health care, better informed patient-centered clinical decisions about comparative efficacy for evidence-based dental practice result from traditional RCT's.